Concrete : microstructure, properties, and materials - Mehte, P. Kumar; Monteiro, Paulo J.M (New York : McGraw Hill Education, 2014)
This thoroughly updated edition contains new information on: recently built construction projects worldwide; shrinkage-reducing admixtures; self-consolidating concrete, pervious concrete, internal curing, and other cutting-edge innovations; modelling of ice formation and alkali-aggregate reaction in concrete; environmental impact of concrete.
PART I: Microstructure and Properties of Hardened Concrete: Introduction -- Microstructure of Concrete -- Strength -- Dimensional Stability -- Durability -- PART II: Concrete Materials, Mix Proportioning, and Early-Age Properties: Hydraulic Cements -- Aggregates -- Admixtures -- Proportioning Concrete Mixtures -- Concrete at Early Age -- Non-destructive Methods -- PART III: Advances in Concrete Technology: Special Types of Concrete -- Concrete Mechanics -- Concrete in the Era of Global Warming and Sustainability.
Includes index.
Keywords: CONCRETE